2 - Modernité et interprétations religieuses - Amin, Samir (Africa Development, 2004)
The advent of modernity in the West is characterized by three main elements: capitalism, democracy and secularism. However, in order to understand this phenomenon, one must consider the role played by the so-called three religions of the Book: Christianity, Judaism, and Islam. Europe achieved modernity by capturing the classic past of the Ancient Greece, which has led to Renaissance. This strategy allowed Renaissance Europe to make the secularisation of social life a basis for modernity, and to decide that individuals could make their own history, and therefore should have the right to innovate and go beyond traditions. The kind of modernity brought about by the Renaissance breaks definitively with the fundamental principle of pre-modern societies, including those of Christian and feudal Europe. However, the 19th century Arab Islamic Renaissance never went beyond the parameters set by Islam, which would have otherwise enabled Muslims to break with traditions, and open up to modern concepts of freedom and democracy. Contemporary political Islam was not an authentic creation of the Muslim people, but was rather invented by the Orientalists in the service of British Imperialism in India. Political Islam, which denies the concept of emancipatory modernity, rejects the very principle of democracy as well as individual and collective rights. This poses a challenge to the development of Africa and the Middle East.